Analysis of thermal comfort and threshold range of airflow supply parameters for different types of work in humid-heat coal mines. (April 2023) - Li, Jiamin; Wu, Lirong; Chen, Hongxuan
Abstract: For the purpose of investigating the effects of various factors as to the thermal comfort of miners, obtaining the most comfortable threshold range of air supply parameters. Five types of jobs with moderate and light labor intensity were selected for the study. The effects of labor intensity, environmental parameters and thermal resistance of clothing on the thermal comfort of miners were analyzed using PMV-PPD index, air motion and temperature difference. Under the same environment, moderate manual workers showed more satisfactory thermal comfort than light manual workers. In a humid and hot mine, the degree of influence of environmental parameters on thermal comfort of workers is ranked as: temperature > humidity > wind speed. Considering the influence of thermal environment and dust on people, the temperature of 27–30 °C, humidity of 40–50% and wind speed of 1.5–2.5 m/s are an optimal combination of ventilation parameters that can simultaneously satisfy human comfort and low energy consumption. The worker can compensate the temperature by adjusting the heat resistance value of the garment. 0.38–2.12clo clothing thermal resistance value, can compensate the temperature range of 27–30 °C. These findings can provide a reference for reducing energy consumption and improving human thermal comfort.